Challenges in ICT integration among Malaysian public primary education teachers: the roles of leaders and stakeholders - Mohamad @ Razak, Nor Asiah; Ab Jalil, Habibah; Ismail, Ismi Arif (International Association of Online Engineering, 2019)
The major role of ICT tools is a means to communicate and collaborate in a globalized, technological world in the knowledge society. In education, the role of ICT is paramount, especially for supporting teachers in ICT integrated teaching. However, little research has been conducted particularly in Asia-Pacific, on the interaction between teachers and ICT integration influenced by their school’s stakeholder, which lead to successful implementation among teachers in teaching. Therefore, the purpose of this study is to investigate the challenges faced by teachers to ICT tools and how the schools' leaders and schools' stakeholders overcome these challenges. By employing a qualitative research methodology, data were collected using a multi-method of data collection, including in-depth interviews, non-participants observations, field notes, and document analysis. The findings uncovered three themes for existing challenges and overcoming challenges. Three themes for the challenges are the inadequate schools’ ICT tools, failure to commit to the schools’ regulations, and failure to comply with the schools’ regulations. The three themes for overcome challenges are assisted performance, sharing ideas, and distributed leadership style. This study can be an exemplar for other schools in strategizing ICT integration for teachers in teaching.